AN ORIGINAL FRAMEWORK FOR GLOBAL LANGUAGE CLASSROOMS: INTEGRATING PHATIC LABOR WITH PEACE THEORY - Mukaddam Khaitova (PUPIL: International Journal of Teaching, Education and Learning, 2026)
In this presentation, I put forward an original conceptual framework to address the critical shortfalls in contemporary language education. I argue that in a world requiring both global and local competence ("glocality"), we must move beyond a narrow focus on linguistic mastery. The proposed framework integrates the novel concept of phatic labor, the systematic work of building classroom belonging, with Johan Galtung’s theories of negative and positive peace. This synthesis offers a new viewpoint on language learning as a process of social participation, where reducing structural barriers (negative peace) is essential but insufficient without intentionally designing for inclusive interaction (positive peace). Grounded in a multi-national synthesis of pedagogical theories, the presentation provides a clear way forward for educators and policymakers seeking to foster student agency, voice, and identity, thereby contributing directly to more equitable and collaborative global learning communities.